27 Palliative care in advanced heart failure. (9th April 2018) - Yuen, Jacqueline K
Abstract : Heart failure (HF) is a chronic, progressive condition associated with high mortality, high symptom burden, and poor quality of life. Acute decompensated HF is one of the leading causes of hospitalisation and poses financial and resource burdens on patients, families, and health care systems. Guidelines from multiple cardiology societies recommend the integration of palliative care into HF management to improve the quality of life and provide support to HF patients and their families. However, the question of how best to deliver palliative care services remains an active area of research. Models of palliative care for HF patients range from episodic inpatient specialty consultation to longitudinal, home-based or outpatient-based co-management or integrated services. Emerging evidence from randomised controlled trials support the provision of longitudinal palliative care alongside usual HF management is associated with improved patient-centred outcomes. However, the impact on acute service utilisation and its cost effectiveness require further research for elucidation.